SWISHMAX SOFTWARE-BASED LEARNING MEDIA SOLUTIONS FOR STUDENTS IN UNDERSTANDING MATHEMATICS - Rosdiana, Rosdiana; Rahma, Nur; Vista, Putri (jfpublisher, 2023)
Technology development in education has become a demand for students and teachers to be able to master it. The selection of appropriate learning media assists teachers in conveying the teaching and learning process in accordance with its objectives. One of those learning media used in this research is Swishmax-Based Learning Media. This media also caused the student more attractive and be motivated in following learning process. Therefore, the objective of this research is to find out the development of learning media based on swishmax software in order to facilitate students in understanding mathematics learning materials. This research used mix method by combining qualitative and quantitative data analysis obtained through questionnaires and student learning outcomes tests. The research results indicate that swishmax learning media is valid, practical and feasible to use in the learning process. The application of this learning media product development is effectively used by obtaining an increase in pre-test and post-test learning outcomes with a good N-Gain score.